2022
DOI: 10.3390/foods11081084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Natural Polysaccharides on Intestinal Microbiota in Inflammatory Bowel Diseases: An Overview

Abstract: The incidence of inflammatory bowel disease (IBD) has increased in recent years. Considering the potential side effects of conventional drugs, safe and efficient treatment methods for IBD are required urgently. Natural polysaccharides (NPs) have attracted considerable attention as potential therapeutic agents for IBD owing to their high efficiency, low toxicity, and wide range of biological activities. Intestinal microbiota and their fermentative products, mainly short-chain fatty acids (SCFAs), are thought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 128 publications
1
8
0
Order By: Relevance
“…The gut microbiota plays an important role in immune metabolism, especially through the influence of metabolites such as SCFAs, bile acids, and amino acids. 36 In the present study, CTX-induction directly triggers changes in the composition of the gut microbiota of mice, as supported by the phenomena of decreased abundance of Bacteroidota and increased abundance of Firmicutes at the phylum level (Fig. 5C).…”
Section: Discussionsupporting
confidence: 74%
“…The gut microbiota plays an important role in immune metabolism, especially through the influence of metabolites such as SCFAs, bile acids, and amino acids. 36 In the present study, CTX-induction directly triggers changes in the composition of the gut microbiota of mice, as supported by the phenomena of decreased abundance of Bacteroidota and increased abundance of Firmicutes at the phylum level (Fig. 5C).…”
Section: Discussionsupporting
confidence: 74%
“…Because gut microbial dysbiosis is often accompanied by abnormal expression of inflammatory cytokines [40], we evaluated the protein levels of TNF-ɑ and IL-6 in colon tissues and confirmed that expression of TNF-ɑ and IL-6 increased in the IBS group compared with the control group (TNF-ɑ: P < 0.01 and IL-6: P < 0.01, respectively). However, treatment of Bifico could restore protein expression to normal levels (TNF-ɑ: the IBS group vs. the IBS + Bifico group: P < 0.05, the control group vs. the IBS + Bifico group: P > 0.05, respectively and IL-6: the IBS group vs. the IBS + Bifico group: P < 0.05, the control group vs. the IBS + Bifico group: P > 0.05, respectively) (Fig.…”
Section: Bifico Reduced the Expression Of Tnf-ɑ And Il-6 In Ibs Micementioning
confidence: 73%
“…It is a high polymer with a molecular weight range of 3.5 kDa to 100 kDa [ 37 ]. Currently, polysaccharides are the most widely studied natural active compounds that enhance innate immunity [ 38 , 39 ]. However, tea pigments, such as TB, have been less studied.…”
Section: Discussionmentioning
confidence: 99%